Поняттєвий складник концепту pain - Yesypenko, Nadia (Видавничий дім "Родовід", 2020)
The article is devoted to the study of the notional component of the concept PAIN. The notion of concept is the basis of cognitive linguistics. This mental entity contains complex information about objects or phenomena and their interpretation in the human mind. Concepts occur as a result of our cognitive activities.Although of classifi cations of concepts varies, almost all the linguists agree on its structure. They single out the nucleus – the prevailing meaning and the peripheral meaning(s) – less prevailing, though still important. In addition, concepts are described as entities consisting of notional, fi gural and evaluative components. Concepts can be studied and understood only through verbalization which varies due to diff erent actors such as age, sex, profession etc.The methods used to establish notional component of the concept comprise etymological analysis and the analysis of defi nitions. In the process of etymological analysis, archaic meanings of the concept have been singled out. The analysis of defi nitions has been conducted on the basis of English lexicographical sources. As a result, one nuclear meaning of the lexeme and seven peripheral meanings have been distinguished. Moreover, synonymic words, which can realize the additional characteristics of the concept, have been analyzed
Keywords: концепт; cтруктура концепту; поняттєвий складник; дефініційний аналіз; етимологічний аналіз